Right Wing Autoritharism, Social Dominance Orientation, Controllability of the Weight and their relationship with antifat attitudes - Magallares, Alejandro; Universidad Nacional de Educación a Distancia, Madrid, España (2013)
Antifat attitudes (AFA) refer to stereotyping based on people’s weight. Literature suggests that people who have an ideologically conservative outlook on life also report negative attitudes toward obese people. Also, it is well established that one of the roots of AFA is the perception that prejudiced individuals have about the controllability of the weight. Therefore, in the current study it is analyzed if Right Wing Autoritharism (RWA, predisposition that individuals have to follow the dictates of a strong leader and traditional and conventional values) and Social Dominance Orientation (SDO, the desire that one’s ingroup dominates other outgroups) predicts prejudice toward obese people and if controllability of the weight mediates this relationship. 456 female students of the UNED (Spanish Open University) from 18 to 35 years were part of the final sample of the study. Results showed that RWA, SDO, controllability and AFA were positively correlated and that the relationship between RWA, SDO and AFA was mediated by the controllability of the weight.